Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Evaluating limits as h--->0?
Heres is a picture of my question
Lim (x+h)^3 - x^3/h
h--->0
How do I go about solving this? I know I'm supposed to plug in x+h wherever there is an h in the first f(x) but then I come out to
((x+h)+h)^3-x^3 divided by h and I have no idea what to do.
2 Answers
- notthejakeLv 79 years ago
(x + h)^3 = x^3 + 3x^2 h + 3 x h^2 + h^3
(x + h)^3 - x^3 = 3x^2 h + 3xh^2 + h^3 = h(3x^2 + 3xh + h^2)
[(x + h)^3 - x^3] / h = h(3x^2 + 3xh + h^2) / h = 3x^2 + 3xh + h^2
as h ==> 0, this goes to 3x^2
lim h ==> 0 is 3x^2